2014
DOI: 10.1038/nature12935
|View full text |Cite
|
Sign up to set email alerts
|

Sensory–motor transformations for speech occur bilaterally

Abstract: Historically, the study of speech processing has emphasized a strong link between auditory perceptual input and motor production output1–4. A kind of ‘parity’ is essential, as both perception- and production-based representations must form a unified interface to facilitate access to higher order language processes such as syntax and semantics, believed to be computed in the dominant, typically left hemisphere5,6. While various theories have been proposed to unite perception and production2,7, the underlying ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
153
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(188 citation statements)
references
References 34 publications
33
153
2
Order By: Relevance
“…However, since we have not directly compared this anatomical prosody network with other specific networks, especially the semantic language processing network, we cannot rule out the possibility that some of the connections also underlie other speech-related, or even general auditory functions. For example, some aspects of speech processing also involve the right hemisphere (Cogan et al, 2014;Hickok and Poeppel, 2007). Further studies are thus needed to determine if the anatomical connections described here are specific for affective prosody processing only, or if they are shared for the processing of other auditory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…However, since we have not directly compared this anatomical prosody network with other specific networks, especially the semantic language processing network, we cannot rule out the possibility that some of the connections also underlie other speech-related, or even general auditory functions. For example, some aspects of speech processing also involve the right hemisphere (Cogan et al, 2014;Hickok and Poeppel, 2007). Further studies are thus needed to determine if the anatomical connections described here are specific for affective prosody processing only, or if they are shared for the processing of other auditory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudowords were created by substituting one phoneme from a matched list of real words. Real words and pseudowords were matched for the following sublexical properties: phonological neighborhood density (range [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], biphoneme probability (range 0.0001-0.0039), and positional probability (range 0.011-0.065). Estimates are in log units, calculated using the Irvine Phonotactic Online Dictionary (31).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, direct intracranial cortical recordings offer a unique opportunity to acquire neural signals with an unprecedented combination of temporal and spatial resolution. Several such studies have implicated the inferior frontal lobe in word production (14)(15)(16)(17)(18)(19), but did not focus on the specific role of Broca's area in production. Conversely, a recent intracranial study was, to our knowledge, the first to focus on Broca's area, finding evidence for lexical, grammatical, and phonological processing (20), but did not examine the processes required for overt word production (phonetic encoding and articulation).…”
mentioning
confidence: 99%
“…However, there are several interesting case studies indicating that damage to the arcuate fasciculus is not a necessary condition for conduction aphasia (Quigg & Fountain, 1999; Quigg, Geldmacher, & Elias, 2006), and that it may not play a specific role in sensorimotor translation (Dick & Tremblay, 2012). There is also recent evidence that the sensorimotor transformations required for verbal repetition are bilateral (Cogan et al, 2014). Furthermore, recent quantitative morphometric neuroimaging analyses have suggested that damage to cortical gray matter in posterior temporo-parietal regions is more closely associated with the repetition deficits observed in a variety of aphasia disorders (Rogalsky et al, 2015).…”
Section: Introductionmentioning
confidence: 99%